Deliciousness of food and a proper balance in fatty acid composition as means to improve human health and regulate food intake. Issue 1 (December 2016) - Mouritsen, Ole
Abstract Diet and lifestyle are not only related to wellbeing but also have dramatic effects on the burdens of ill health and non-communicable diseases. Drawing upon anthropological evidence for human evolution and the chemistry of the brain, as well on the physiology of taste, a brief review is provided on the effects of food composition and food flavor on health, wellbeing, and the quality of life. Our ancestors' access to the particular fatty acids of marine food sources and man's early use of the fire to heat-treat food have been prime determinants for the evolution of our relatively big brains and our craving for foodstuff characterized by sweet and umami flavors. The increasing unbalance of fatty acids in our diets appears to have severe effects on the condition of our neural system and the brain, leading to a severe increase in brain disorders and mental diseases. Similarly, a lack of deliciousness in prepared meals may be a possible reason for poor nutritional management and excess intake of sugar, salt, and fat. These changed conditions are suggested as reasons why our brain, the flavor of our food, and hence our health are under siege.